Konceptualne spremembe v odločanju o varstvu in vzgoji otroka ter stikih v primerih nasilja - Leskošek, Vesna (Socialno delo, 2025)
The main topic of the paper is the changes to the Family Code in the section dealing with divorce, custody and visitation right. The changes reflect a transformed understanding of the relationship between the partners and the relationship with the children, which on the surface represents progress towards a more equal position of men and women in divorce and custody proceedings, but an analysis of the commentaries on the Family Code shows that the practices are conservatively patriarchal and based on the belief that women are primarily responsible for the children's good relationship with the noncustodial parent, i.e. mainly the father. An analysis of the texts of court decisions since the Family Code came into force shows that the changes follow the concept of parental alienation, which is also used in cases where the divorce was a result of gender-based violence and which allows for the continuation of violent control after the divorce. The article concludes with a list of the main international instruments that this jurisprudence violates, including the Istanbul Convention, which Slovenia ratified in 2014.
Keywords: child’s interests; children's rights; coercive control; Družinski zakonik; Family Code; gender stereotypes; koristi otroka; nasilje; nasilni nadzor; otrokove pravice; parental alienation; spolni stereotipi; starševsko odtujevanje